Global prevention and control of chronic non-communicable diseases: the action and role of the World Health Organization - Yawen JIA; Zongbin WANG; Ji ZHANG; Na LI; Minmin WANG; Yanan LUO; Yinzi JIN (Editorial Office of Chinese Journal of Public Health, 2023)
Non-communicable diseases (NCDs) are currently a major global health challenge and one of the core issues of concern to the World Health Organization (WHO). As populations' aging, middle- and low-income countries face a double burden of communicable diseases and NCDs, with a serious pressure on health systems of the countries. In this paper, we summarize the role of and challenges to the WHO in promoting global control of NCDs, and make recommendations for the development of global NCD prevention and control strategies.